Immune-related aseptic meningitis and strategies to manage immune checkpoint inhibitor therapy: a systematic review - Nannini, Simon; Koshenkova, Larysa; Baloglu, Seyyid; Chaussemy, Dominique; Noël, Georges; Schott, Roland (Journal of neuro-oncology, 2022)
Introduction Immune checkpoint inhibitors (ICIs) can induce adverse neurological effects. Due to its rarity as an adverse effect, meningitis has been poorly described. Therefore, meningitis diagnosis and management can be challenging for specialists. Moreover, meningitis can be an obstacle to resuming immunotherapy. Given the lack of alternatives, the possibility of reintroducing immunotherapy should be discussed on an individual basis. Here, we present a comprehensive systematic review of meningitis related to ICIs. Review We performed a search for articles regarding immune-related meningitis published in PubMed up to November 2021 with the MeSH terms “meningitis” and “immune checkpoint” using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method. We summarized the studies not only by category but also based on whether it was a primary article or case report to provide a systematic overview of the subject. We reviewed a total of 38 studies and herein report the clinical experiences, pharmacovigilance data and group knowledge from these studies. Conclusion This review summarizes the existing information on immune-related meningitis and the possibility of reintroducing immunotherapy after the development of central neurological side effects. To the best of our knowledge, there is little information in the literature to guide clinicians on decisions regarding whether immunotherapy should be continued after a neurological adverse event occurs, especially meningeal events. This review emphasizes the necessity of systematic examinations, steroid treatment (as a cornerstone of management) and the need for further exploratory studies to obtain a clearer understanding of how to better manage patients who experience these side effects. The findings summarized in this review can help provide guidance to practitioners who face this clinical situation.